A centrifugal pathway to the mouse accessory olfactory bulb from the medial amygdala conveys gender-specific volatile pheromonal signals - Martel, Kristine L.; Baum, Michael J. (The European journal of neuroscience, 2009)
We previously found that female mice exhibited Fos responses in the accessory olfactory bulb (AOB) after exposure to volatile opposite‐sex, but not same‐sex, urinary odours. This effect was eliminated by lesioning the main olfactory epithelium, raising the possibility that the AOB receives information about gender via centrifugal inputs originating in the main olfactory system instead of from the vomeronasal organ. We asked which main olfactory forebrain targets send axonal projections to the AOB, and whether these input neurons express Fos in response to opposite‐sex urinary volatiles. Female mice received bilateral injections of the retrograde tracer cholera toxin B (CTB), into the AOB, and were exposed to either same‐ or opposite‐sex volatile urinary odours 1 week later. We found CTB‐labeled cell bodies in several forebrain sites including the bed nucleus of the accessory olfactory tract, the rostral portion of the medial amygdala (MeA) and the posteromedial cortical nucleus of the amygdala. A significant increase in the percentage of CTB/Fos co‐labeled cells was seen only in the MeA of female subjects exposed to male but not to female urinary volatiles. In Experiment 2, CTB‐injected females were later exposed to volatile odours from male mouse urine, food, or cat urine. Again, a significant increase in the percentage of CTB/Fos co‐labeled cells was seen in the MeA of females exposed to male mouse urinary volatiles but not to food or predator odours. Main olfactory–MeA–AOB signaling may motivate approach behaviour to opposite‐sex pheromonal signals that ensure successful reproduction.